Comparative evaluation of effects of combined oral anti-diabetic drugs (sulfonylurea plus pioglitazone and sulfonylurea plus metformin) over lipid parameters in type 2 diabetic patients - Sen, Sukanta; Sinha, Satwika; Gupta, K. K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Type 2 diabetes is associated with significant cardiovascular morbidity and mortality. Dyslipidemia, which affects almost 50% of patients with type 2 diabetes, is a cardiovascular risk factor characterized by elevated triglyceride levels, low high-density lipoprotein (HDL) cholesterol levels, and a preponderance of small, dense, low-density lipoprotein (LDL) particles. In addition to their glucose-lowering properties, oral anti-diabetic agents may have effects on lipid levels, especially triglycerides (TGs), HDL-C, LDL-C and total cholesterol levels. Methods: A prospective, open-labeled, randomized, parallel-group study was carried out in sizable number of patients (n=40) of established type 2 diabetes on combined oral anti-diabetic drugs, to investigate the effects of combined oral anti-diabetic on lipid parameters who was not receiving any hypolipidemic agent in addition. Results: Statistically significant mean reduction of triglycerides (TGs) of 25.1mg/dl (a 15.30% reduction from baseline value) and by 13.5 mg/dl (a 8.94% reduction from baseline value) in the SU (sulfonylurea) plus PIO (pioglitazone) and SU plus MET (metformin) group respectively. Present study also shows improvement in HDL cholesterol with SU plus PIO group by 13.18% which is almost twice that observed in SU plus MET group (8.06%). Present study also shows increase in LDL cholesterol with SU plus PIO group by 2.10%, is just opposite to SU plus MET group (4.92 % decrease). With SU plus PIO group, a statistically significant mean reduction of total cholesterol (TC) of 8.33mg/dl (5.14 % decrease) and by 7.62 mg/dl (4.28% decrease) in the SU plus MET group. Conclusions: Pioglitazone, a thiazolidinedione, has been shown to improve the lipid profile in patients with type 2 diabetes by increasing HDL-C levels and by decreasing triglyceride and total cholesterol levels in monotherapy or combination regimens with sulfonylurea. Metformin also has been shown to reduce LDL-C, TC, and TG levels and increase HDL-C levels in monotherapy and in combination regimens with sulfonylurea. In contrast, LDL cholesterol levels mild increase with pioglitazone monotherapy or with SU combination therapy. Thus the results of this study have demonstrated that SU plus pioglitazone is an effective combination regimen for patients insufficiently treated with SU monotherapy and may provide possible positive effects on other coronary risk factors/ dyslipidemias associated with the type 2 diabetes.